The development of KPI for measuring ICT support service quality - Nor, Rozi Nor Haizan; Alias, Rose Alinda; Abdul Rahman, Azizah (Departemen Sistem Informasi, Institut Teknologi Sepuluh Nopember, 2013)
This paper proposes a development of key performance indicators (KPIs) for measuring the quality of ICT support services. The usage of Information and Communication Technology (ICT) cannot be denied in every stage of work by individuals, businesses or organizations. Hence, various categories of ICT services (ICTS) including ICT support services have become important activities that need to be measured from time to time to ensure the advantages of ICT usage. ICT support services had been revealed as one of the five main ICTS categories within the context of Malaysian Universities (MUs). This category of ICTS is referred to as general assistance related to providing ICTS to users. While ICT application systems services and ICT infrastructure services are considered as core services, ICT support services are regarded as peripheral services that indirectly assist ICTS implementation. In part of service quality studies including ICTS, it was proven that previous researches had discussed the assessment, measurement and improvement of their service quality by proposing related models or frameworks. However, there is still a lack of producing a quantifiable approach to measure the ICT service quality (ICTSQ) including the ICT support services. Most of the previous researches were only focused on the initial stage of service quality assessment and measurement. Most of them had only concern on analyzing and identifying various quality factors and attributes based on the context involved. Thus, this paper proposes the development of KPI as being the latest and most effective measureable approach for measuring the quality of ICT support services. This study reviewed the current scope of ICT support services, quality factors and attributes before the KPIs is developed. The investigation is done within the context of Malaysian Universities (MUs). Interviews to ICT support services’ stakeholders were conducted within the context to get the empirical data. The KPI development model is intended to provide ideas and guidelines for the purpose of measuring this ICTS.